Design Model of Rectangular Concrete-Filled Steel Tubular Stub Columns under Axial Compression - Faesal Alatshan; Siti Aminah Osman; Abdelmajeed Altlomate; Mohammed Alkair; Roszilah Hamid; Fidelis Mashiri (Buildings, 2023)
This research collected and summarized a total of 455 experimental tests of axially loaded square and rectangular concrete-filled steel tubular (CFST) stub columns. The recently published papers were used to evaluate the current design equations from four international standards, namely the American Concrete Institute (ACI) code, British Standard (BS5400), Chinese standard (BDJ13-51), and Eurocode 4 (EC4). It was found that the results obtained from the codes have appreciable differences and could be improved, especially for the specimens fabricated using high-resistance materials. Therefore, new empirical equations were proposed based on the four standard formulas and the wide range of previously available experimental data to provide more accurate estimations. The proposed equations could predict an average sectional capacity of only 0.1% lower than the experimental results, with better data scattering than the existing equation’s results.